Kontribusi Jurnalisme Warga sebagai Strategi Perluasan Jenis Konten Berita di Liputan6.com - Fahmi Zaenal Mutakin; Achmad Wildan Kurniawan; Feri Purnama (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Public participation in digital information production encourages the development of citizen journalism, one of which is through the Citizen6 channel on Liputan6.com. This channel allows the public to contribute news content. This study aims to determine the contribution of citizen journalism as a strategy to expand the type of news content, as well as its impact on the quality and diversity of information. The research used a descriptive qualitative method with interviews, observations, documentation, and literature studies, where the approach is known as a triangulation technique, which is a method that combines various ways of collecting data in order to obtain more accurate information from various sources. Researchers analysed this research through Media Ecology theory. The results showed that citizen journalism plays a role in enriching the variety of topics, especially the categories of human interest, lifestyle, technology, and social issues. This participation creates an inclusive media ecosystem, while maintaining the curation process by professional editors. Collaboration between citizen journalists and professionals is proven to enrich content and maintain media credibility. It is recommended that the media continue to improve training, editing, and strengthen interaction with contributors to maintain quality and expand public participation.